Valeriy Sagaydachny: unknown pages of biography - Omelchenko, Tetyana (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The 85th anniversary of the birth of the outstanding Ukrainian pianist, Honored Artist of Ukraine, Professor of the Kyiv Conservatory Valery Mikhailovich Sahaidachny (1939–2009) has brought to the fore the issue of studying and clarifying some facts of his creative biography. The name of the Ukrainian pianist Valeriy Sahaidachny is rightfully included in the book “2000 Outstanding Musicians of the 20th Century”. He was a bright performer, a subtle and thoughtful musician, who possessed a strong artistic temperament, an outstanding level of pianistic skill. During his creative life, he successfully performed in Ukraine, Spain, Germany, Poland, Greece, the USA, Canada,. He included the most complex works of a wide stylistic range in his solo programs, but he especially skillfully performed and interpreted the works of Chopin. Valeriy Sahaidachny raised a whole galaxy of bright students, many of whom are the pride of the Ukrainian piano school. The main objective of the study is to find out the circumstances of Sahaidachny’s life and education, in particular, the period of the artist’s initial musical education, which had not previously been covered in autobiographical materials. The methodology includes the method of biographical reconstruction. Based on archival documents from a private collection and the memoirs of Sahaidachny’s friends, it was possible to reconstruct this important chronological period in the formation of the musician, and for the first time to publish the name of his first teacher. In was Olga Antonivna Skoropostyzhna, student of Volodymyr Puhalsky. The memoirs of contemporaries and archival documents are presented, which testify to the progressiveness of her methodology for teaching piano, focused on involving the child in music lessons in early childhood. The level of her professional competence allowed to prepare the student for admission to secondary and higher musical educational institutions. The personality of Olga Skoropostyzhna is presented in the context of her friendly and professional ties with famous representatives of the national artistic elite: A. Artobolevska, S. Richter, D. Kabalevsky, the family of artists and art historians Prakhov. Results and conclusions. It is assumed that the name of Olga Skoropostyzhna was not made public by Valery Sahaidachny because of her husband, a priest — the rector of the Volodymyr Cathedral in Kyiv, the teacher at the Kyiv Theological Seminary: in the Soviet era of ideological persecution of the church and believers, such close communication with the priest’s family could have negative consequences for the person. Thus, a holistic idea is formed about the fundamental nature of Valery Sahaidachny’s primary and secondary musical education, the roots of which are closely connected with the Kyiv Piano School and its founder — Volodymyr Puhalsky.